Heterogeneous Photodecolorization of Methyl Green Catalyzed by Fe(II)-o-Phenanthroline/Zeolite Y Nanocluster - Alireza Nezamzadeh-Ejhieh; Elahe Shahriari (International Journal of Photoenergy)
The potential of Fe(II)-orthophenatrolin, as doped with synthetic zeolite Y nanocluster (Na-Y) via complexation process, after wet impregnation of parent zeolite with FeSO4 aqueous solution, was studied as a photocatalyst in decolorization of Methyl Green (MG) under UV irradiation. The characterization of the synthesized zeolite nanocluster and the prepared catalyst was studied using X-ray powder diffraction (XRD), infrared spectroscopy (FT-IR), thermal analysis, and SEM methods. The dye photodecolorization process was studied considering the influence of experimental parameters and it was observed that photoreactivity of the photocatalyst was varied with catalyst amount, initial dye concentration, pH of dye solution, temperature, and the presence of KBrO3. The optimal experimental parameters were obtained as follows: catalyst amount: 1 gL−1, dye concentration: 40 ppm, pH: 9, and active component value: 100 mg Fe(II)-orthophenatrolin per g catalyst. The reusability of the intended catalyst was also investigated. The degradation process obeyed first-order kinetics.